Local delivery of low-dose anti-CTLA-4 to the melanoma lymphatic basin leads to systemic Treg reduction and effector T cell activation - van Pul, Kim M; Notohardjo, Jessica C L; Fransen, Marieke F; Koster, Bas D; Stam, Anita G M; Chondronasiou, Dafni; Lougheed, Sinéad M; Bakker, Joyce; Kandiah, Vinitha; van den Tol, M Petrousjka; Jooss, Karin; Vuylsteke, Ronald J C L M; et al. (Science immunology, 2022)
Preclinical studies show that locoregional CTLA-4 blockade is equally effective in inducing tumor eradication as systemic delivery, without the added risk of immune-related side effects. This efficacy is related to access of the CTLA-4 blocking antibodies to tumor-draining lymph nodes (TDLNs). Local delivery of anti-CTLA-4 after surgical removal of primary melanoma, before sentinel lymph node biopsy (SLNB), provides a unique setting to clinically assess the role of TDLN in the biological efficacy of locoregional CTLA-4 blockade. Here, we have evaluated the safety, tolerability, and immunomodulatory effects in the SLN and peripheral blood of a single dose of tremelimumab [a fully human immunoglobulin gamma-2 (IgG2) mAb directed against CTLA-4] in a dose range of 2 to 20 mg, injected intradermally at the tumor excision site 1 week before SLNB in 13 patients with early-stage melanoma (phase 1 trial; NCT04274816). Intradermal delivery was safe and well tolerated and induced activation of migratory dendritic cell (DC) subsets in the SLN. It also induced profound and durable decreases in regulatory T cell (Treg) frequencies and activation of effector T cells in both SLN and peripheral blood. Moreover, systemic T cell responses against NY-ESO-1 or MART-1 were primed or boosted (N = 7), in association with T cell activation and central memory T cell differentiation. These findings indicate that local administration of anti-CTLA-4 may offer a safe and promising adjuvant treatment strategy for patients with early-stage melanoma. Moreover, our data demonstrate a central role for TDLN in the biological efficacy of CTLA-4 blockade and support TDLN-targeted delivery methods.Preclinical studies show that locoregional CTLA-4 blockade is equally effective in inducing tumor eradication as systemic delivery, without the added risk of immune-related side effects. This efficacy is related to access of the CTLA-4 blocking antibodies to tumor-draining lymph nodes (TDLNs). Local delivery of anti-CTLA-4 after surgical removal of primary melanoma, before sentinel lymph node biopsy (SLNB), provides a unique setting to clinically assess the role of TDLN in the biological efficacy of locoregional CTLA-4 blockade. Here, we have evaluated the safety, tolerability, and immunomodulatory effects in the SLN and peripheral blood of a single dose of tremelimumab [a fully human immunoglobulin gamma-2 (IgG2) mAb directed against CTLA-4] in a dose range of 2 to 20 mg, injected intradermally at the tumor excision site 1 week before SLNB in 13 patients with early-stage melanoma (phase 1 trial; NCT04274816). Intradermal delivery was safe and well tolerated and induced activation of migratory dendritic cell (DC) subsets in the SLN. It also induced profound and durable decreases in regulatory T cell (Treg) frequencies and activation of effector T cells in both SLN and peripheral blood. Moreover, systemic T cell responses against NY-ESO-1 or MART-1 were primed or boosted (N = 7), in association with T cell activation and central memory T cell differentiation. These findings indicate that local administration of anti-CTLA-4 may offer a safe and promising adjuvant treatment strategy for patients with early-stage melanoma. Moreover, our data demonstrate a central role for TDLN in the biological efficacy of CTLA-4 blockade and support TDLN-targeted delivery methods.